(untitled) (GEON Journal (Management, Organizations and Business), 2018)
This document is the result of a literature review and an effort to organize the ideas expressed by several thinkers of a great sociologist and economist such as Max Weber, in order to open a debate about economic thought. To this end, ideas were taken from various authors and key texts to understand the traced themes, which are combined with ideas for the final result.